2001
DOI: 10.1128/aem.67.12.5683-5693.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Sigma Factor AlgU (AlgT) Controls Exopolysaccharide Production and Tolerance towards Desiccation and Osmotic Stress in the Biocontrol Agent Pseudomonas fluorescens CHA0

Abstract: A variety of stress situations may affect the activity and survival of plant-beneficial pseudomonads added to soil to control root diseases. This study focused on the roles of the sigma factor AlgU (synonyms, AlgT, RpoE, and 22 ) and the anti-sigma factor MucA in stress adaptation of the biocontrol agent Pseudomonas fluorescens CHA0. The algU-mucA-mucB gene cluster of strain CHA0 was similar to that of the pathogens Pseudomonas aeruginosa and Pseudomonas syringae. Strain CHA0 is naturally nonmucoid, whereas a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 70 publications
6
96
0
1
Order By: Relevance
“…Microarray analysis revealed that AlgT exerts broad-range regulatory effects on approximately 6 % of the P. aeruginosa genome, with alginate and flagellar genes accounting for only one-fifth of AlgT-regulated genes (Tart et al, 2005). AlgT was found to be essential for the tolerance of a P. fluorescens biocontrol strain towards desiccation and osmotic stress (Schnider-Keel et al, 2001). A P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray analysis revealed that AlgT exerts broad-range regulatory effects on approximately 6 % of the P. aeruginosa genome, with alginate and flagellar genes accounting for only one-fifth of AlgT-regulated genes (Tart et al, 2005). AlgT was found to be essential for the tolerance of a P. fluorescens biocontrol strain towards desiccation and osmotic stress (Schnider-Keel et al, 2001). A P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) The sigma factor RpoE plays a major role in maintaining the integrity and function of the envelope and provides resistance to environmental stresses including desiccation and oxidative stress in Pseudomonas spp. (4,37,38). (iii) The domain structure of PhyR shows that the predicted phosphorable receiver domain is located at the C terminus (Fig.…”
Section: A Response Regulator Common To Alphaproteobacteria Essentialmentioning
confidence: 99%
“…The up-regulation of algU in osmotically shocked cells (Table 3) was expected given that AlgU has previously been shown to control the expression of genes in Pseudomonas species that confer resistance under a variety of stress conditions, including elevated osmolarity (9,15). Furthermore, the observation that ORFs PA3459 to PA3461-encoding putative osmoprotectant synthesis proteins-play a significant role in osmoadaptation is consistent with the report by Firoved et al (6) that expression of PA3459 is AlgU dependent.…”
mentioning
confidence: 97%